ARSITEKTUR BERKELANJUTAN DI BULUTANA KECAMATAN TINGGIMONCONG KABUPATEN GOWA SULAWESI SELATAN - Syarief Beddu (Teknosains, 2011)
Sustainable architecture  that also called green architecture, is the new trend in the world architecture as consequence of  PBB’s commission. This research have fenomenologis with qualitative method  All result of notching which born the including architecture which ever mean nature as part of pattern subsistence of subsistence of them. Society of Bulutana as society of tradisional-agraris, in developing its settlement pattern and its life, pursuant to smart natural existence ve wisdom in executing going concern development. Architecture values  have continuation old, included in management of its environment. Exploiting natural potency represent the part of arranging local wise value preserveing hit herto. Target of Obyek research is Balla Lompoa and Balla Jambua, representing historic building situs. Research location in Bulutana, High district of Snout, in Gowa  regency.